Performance of bicontinuous structural electrolytes. Issue 2 (25th May 2020) - Tu, Vinh; Asp, Leif E; Shirshova, Natasha; Larsson, Fredrik; Runesson, Kenneth; Jänicke, Ralf
Abstract: Structural power composites are multifunctional materials with simultaneous load bearing and energy storing functionality. This is made possible due to carbon fibers' ability to act not only as structural reinforcement materials, but also as electrode components. A crucial component of structural power composites is the structural electrolyte that is required to have both high stiffness and high ionic conductivity. To explore microstructure properties that bear optimal bifunctional performance a procedure is presented to generate various classes of synthetic microstructures with a wide span of properties for computer simulation. The effective properties of the generated artificial structural electrolytes are obtained via virtual material testing and compared with experimentally obtained data. Ultimately, a microstructure class with very good bifunctional properties is identified.